2011
DOI: 10.1111/j.1365-2745.2011.01801.x
|View full text |Cite
|
Sign up to set email alerts
|

Niche overlap reveals the effects of competition, disturbance and contrasting assembly processes in experimental grassland communities

Abstract: Summary 1.Understanding the processes by which species sort themselves into communities remains a central puzzle for attempts to maintain biodiversity. It remains unclear whether any single assembly process is generally dominant or whether the influence of contrasting processes varies in a predictable way relative to biotic and abiotic gradients. Abundance-weighted niche overlap between species provides a powerful means of contrasting two major assembly processes -niche complementarity and environmental filter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
263
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(294 citation statements)
references
References 60 publications
25
263
2
4
Order By: Relevance
“…While a small number of studies have examined the effects of spatial scale on community assembly, a greater number of them have investigated changes in assembly patterns across different disturbance regimes (see, for example, Pausas & Verd 2008;Mason et al 2011;Bernard-Verdier et al 2012;Lalibert e, Norton & Scott 2013). Theoretical predictions and conclusions about the way in which disturbance regimes may influence convergence and divergence patterns vary between studies, depending on the type and intensity of the disturbance regime, but also on the fact that disturbance effects on species coexistence are expected to change across biomes and productivity gradients (Pickett & White 1985;Lalibert e, Norton & Scott 2013).…”
Section: S T U R B a N C E E F F E C T Smentioning
confidence: 99%
See 2 more Smart Citations
“…While a small number of studies have examined the effects of spatial scale on community assembly, a greater number of them have investigated changes in assembly patterns across different disturbance regimes (see, for example, Pausas & Verd 2008;Mason et al 2011;Bernard-Verdier et al 2012;Lalibert e, Norton & Scott 2013). Theoretical predictions and conclusions about the way in which disturbance regimes may influence convergence and divergence patterns vary between studies, depending on the type and intensity of the disturbance regime, but also on the fact that disturbance effects on species coexistence are expected to change across biomes and productivity gradients (Pickett & White 1985;Lalibert e, Norton & Scott 2013).…”
Section: S T U R B a N C E E F F E C T Smentioning
confidence: 99%
“…It is generally assumed that trait divergence will be stronger under moderately disturbed conditions (Grime 2006) -such as those in traditionally grazed or mown grasslands (Grubb 1986) -where biomass removal should decrease the chance of competitive exclusion of species that bear traits associated with low competitive ability (Mayfield & Levine 2010). However, it has also been observed that a lack of biomass removal in grasslands may enhance niche differentiation and promote functional divergence between species in response to greater competition for light (Mason et al 2011). The abandonment of traditional grassland management may therefore potentially result in either increased divergence or increased convergencedepending on the site conditions.…”
Section: S T U R B a N C E E F F E C T Smentioning
confidence: 99%
See 1 more Smart Citation
“…The selection and complementarity effects distinguish the effects of very productive and dominant species to the complementarity in resource utilization by different species. Three grassland communities of six grass species across four management treatments (two cut frequencies and two levels of nitrogen fertilization) and throughout 2 years were explored in this study (n=24 for species assembling (Mason et al 2011;Spasojevic and Suding 2012;Gerhold et al 2013;Laliberté et al 2013;Price et al 2014;Carboni et al 2014). For instance, along an environmental severity gradient in productive grassland communities, Maire et al (2012a, see also Bernard-Verdier et al 2012 as another example along a natural soil fertility gradient in Mediterranean rangelands) found that convergence pattern towards high plant stature traits was the predominant force to explain species abundance in fertile and less disturbed habitat.…”
Section: Which Traits For Which Assembly Process?mentioning
confidence: 99%
“…近年来, 随着全球生物多样性的快速降低, 生 物多样性与生态系统功能的关系成为生态学领域备 受关注的科学问题 (Chapin et al, 2000)。生态系统生 产力是反映生态系统功能的最为综合的指标(如碳 氮循环、枯落物分解、动物采食等) (Chapin et al, 2000;Naeem, 2002) Leibold, 1998;Grime, 2006;Mayfield & Levine, 2010); 二是共存物种间的生态 位分化又会促使性状趋异, 引起FD增加 (Macarthur & Levins, 1967;Navas & Violle, 2009;Mouchet et al, 2010;Mason et al, 2011), FD对施肥的响应取决于 这两种机制的平衡 (Niu et al, 2014 …”
unclassified